Continuous extracorporeal stool-transport system: a new and economical procedure for transitory short-bowel syndrome in prematures and newborns - Schäfer, Klemens; Zachariou, Zacharias; Löffler, W.; Daum, Roland (Pediatric surgery international, 1997)
Between May 1994 and June 1995, nine newborns underwent surgery due to mechanical ileus or intrauterine perforation of the small bowel. Three were very-low-birth-weight infants weighing between 520 and 1,200 g. Surgery was performed in the first 2 days of life and split ileo- or jejunostomas were implanted. Early oral nutrition was initiated. To avoid non-use of the distal bowel and shortbowel syndrome, the aboral stoma was irrigated a few days later with the proximal feces. A new technique was applied to transport the chyle continuously from the oral to the aboral stoma: the stool was collected in an especially constructed stoma bag and transported distally by a roller pump. No major complications were seen. The general outcome was excellent in all cases, and reanastomosis under optimal bowel conditions was achieved in all patients without further problems.
Elektronische Reproduktion der Druck-Ausgabe 10. September 2013
Gesehen am 09.09.2024